Light-driven S-type heterojunction photo-anode film with integrated anti-corrosion and anti-fouling functions and preparation method of light-driven S-type heterojunction photo-anode film

By constructing an S-shaped heterojunction photoanode film, the problem of the single function of photoanode materials is solved, realizing integrated anti-corrosion and anti-fouling in the marine environment, improving photoelectric conversion efficiency and protective effect, and providing a green and efficient marine engineering protection solution.

CN120989626APending Publication Date: 2025-11-21QINGDAO UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511517240.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-23
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

Existing photoanode materials have limited functionality in marine environments and cannot effectively address electrochemical corrosion, biological corrosion, and algal adhesion simultaneously. Furthermore, their high photogenerated carrier recombination rate and narrow solar response range result in low photoelectric conversion efficiency.

Method used

The S-shaped heterojunction structure is composed of a first semiconductor material and a second semiconductor material to form a heterojunction photoanode film with an S-shaped electron transfer path. The photogenerated carriers are directionally recombined and spatially separated by the built-in electric field at the interface, while retaining electrons with strong reducing ability and holes with strong oxidizing ability, thus achieving integrated corrosion and fouling prevention.

Benefits of technology

It achieves efficient anti-corrosion, anti-fouling and algae suppression functions in marine environments, extends the lifetime of photogenerated carriers, and synchronizes the output of electron and hole active substances, providing strong reduction electrons and efficient oxidation capabilities. It breaks through the bottleneck of weakened redox capabilities of traditional heterojunctions, providing green, efficient and long-lasting protection for marine engineering facilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120989626A_ABST
    Figure CN120989626A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of corrosion inhibition of metal materials of ocean engineering structures, and particularly relates to a light-driven S-type heterojunction photo-anode film integrating anti-corrosion and anti-fouling functions and a preparation method of the light-driven S-type heterojunction photo-anode film. In order to solve the problem that the existing protection technology is difficult to efficiently realize corrosion prevention and pollution prevention at the same time, two semiconductor materials with matched energy band structures are compounded to construct a heterojunction structure with an S-shaped electron transfer path. The S-shaped heterojunction can efficiently promote separation and migration of photo-induced electron-hole pairs: the photo-induced electrons migrate to a metal substrate, so that lasting photoelectrochemical cathode protection is provided, and corrosion prevention is realized; meanwhile, photogenerated holes and active oxygen species generated on the surface of the material can effectively degrade organic pollutants and inhibit attachment of microorganisms and algae, and antifouling is achieved. According to the invention, synergism and enhancement of corrosion prevention, pollution prevention and algae inhibition under illumination are realized, and a green and efficient new strategy is provided for long-term protection of ocean engineering facilities.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of corrosion inhibition of marine engineering structure metal materials, and particularly relates to a light-driven anti-corrosion and anti-fouling integrated S-type heterojunction photoanode film and a preparation method thereof. BACKGROUND

[0002] The long-term protection of marine engineering equipment depends on the precise regulation of the physical and chemical processes of material interfaces. Currently, single-function materials have been unable to cope with the synergistic attack of corrosion ions, microorganisms, organic matter and other multi-component media in the marine environment, and the development of multi-functional material systems with both electronic regulation and chemical activity regulation capabilities has become an important trend.

[0003] In the field of light-driven protective materials, wide-bandgap semiconductors (such as TiO2 and ZnO) have light stability, but their high photogenerated carrier recombination rate and narrow solar response range limit the photoelectric conversion efficiency. Although the light absorption and charge separation behavior can be improved by means of noble metal deposition and ion doping, such modifications are often complex and costly, and the ability to regulate the intrinsic electronic structure of the material is limited.

[0004] Heterojunction engineering is an effective strategy to break through the performance bottleneck of single materials. Traditional type II heterojunctions can achieve spatial separation of electrons and holes, but the charge migration mechanism causes oxidation and reduction reactions to occur on two materials, resulting in weakened overall redox capacity. For example, electrons migrate to semiconductors with a more positive reduction potential (more negative conduction band position), and holes migrate to semiconductors with a more negative oxidation potential (more positive valence band position), resulting in the inability to provide strong reducing electrons for efficient cathodic protection and the inability to generate strong oxidizing holes to decompose organic fouling or kill microorganisms. This intrinsic "ability loss" mechanism fundamentally limits its application in multiple protection scenarios.

[0005] In recent years, the proposal of S-type (step-type) heterojunctions has provided a new paradigm for material design. This structure forms an internal electric field at the interface of two semiconductors with matching band structures, driving the directional recombination of photogenerated carriers, not only achieving efficient spatial separation, but also selectively retaining electrons with the strongest reducing ability and holes with the strongest oxidizing ability. This "selective" charge separation mechanism fundamentally solves the contradiction between carrier recombination and reduced redox capacity, providing an unprecedented material basis for simultaneously achieving "cathodic protection (strong reduction)" and "bactericidal and antifouling (strong oxidation)" in the same material system.

[0006] However, how to screen and design S-type heterojunction materials with suitable energy band structure, good interface compatibility and environmental stability according to the characteristics of marine environment, and optimize the micro-morphology and macro-structure to construct high-efficiency, stable and engineeringable multifunctional protective coating for marine is still a key challenge and major opportunity for current material research. SUMMARY

[0007] The application aims to provide a light-driven S-type heterojunction photoanode film with integrated anti-corrosion and anti-fouling functions and a preparation method thereof, so as to help the redox activity of the photoanode, solve the problems of single function of the photoanode, low solar energy utilization rate and inability to simultaneously cope with electrochemical corrosion, biological corrosion and algae adhesion, and provide a new and green and efficient solution for long-term protection of marine engineering facilities.

[0008] In order to achieve the above-mentioned purpose, the application provides the following technical scheme: a light-driven S-type heterojunction photoanode film with integrated anti-corrosion and anti-fouling functions, characterized in that the film is composed of a first semiconductor material and a second semiconductor material; the conduction band minimum energy level of the first semiconductor material is lower than that of the second semiconductor material, and the valence band maximum energy level of the first semiconductor material is lower than that of the second semiconductor material; after Fermi energy level balance, the energy bands of the two semiconductor materials are bent at the interface, the photo-generated electrons of the second semiconductor material and the photo-generated holes of the first semiconductor material are combined, and a heterojunction structure with an S-type electron transfer path is formed.

[0009] The conduction band minimum energy level of the first semiconductor material is lower than the reduction potential of Fe 2 ⁺ / Fe (-0.44 V vs. NHE), preferably one of indium sulfide (In2S3), bismuth oxyiodide (BiOI), manganese indium sulfide (MnIn2S4) and copper indium sulfide (CuInS2);

[0010] The valence band maximum energy level of the second semiconductor material is higher than the oxidation potential of O2 / H2O (+1.23 V vs. NHE), preferably one of bismuth molybdate (Bi2MoO6), manganese tungstate (MnWO4), nickel titanate (NiTiO3) and silver iodide (AgI).

[0011] The application also provides a preparation method of the light-driven S-type heterojunction photoanode film with integrated anti-corrosion and anti-fouling functions, which adopts the following technical scheme: (1) providing a first semiconductor precursor and a second semiconductor precursor; (2) reacting the first semiconductor precursor and the second semiconductor precursor by a hydrothermal method, a calcination method, an in-situ growth method or an ultrasonic mixing method to make the first semiconductor material and the second semiconductor material composite, thereby forming the S-type heterojunction photoanode film.

[0012] The reaction temperature of the hydrothermal method is preferably 120-180 DEG C; the reaction time of the hydrothermal method is preferably 6-24 hours.

[0013] The heat treatment temperature of the calcination method is preferably 300-500 DEG C; the holding time of the calcination method is preferably 1-4 hours.

[0014] The application also provides an application of the S-type heterojunction photoanode film with integrated anti-corrosion and anti-fouling functions driven by light, which adopts the following technical scheme: the application of the S-type heterojunction photoanode film in metal material surface protection.

[0015] The application preferably simultaneously realizes the anti-corrosion and anti-fouling and algae inhibition functions in a marine environment.

[0016] Beneficial effects:

[0017] The most remarkable beneficial effect of the application is that the S-type (step-type) heterojunction structure is designed and constructed, and the single material system successfully realizes the integrated protection of marine corrosion and biological fouling. The core advantage lies in the unique charge separation mechanism of the S-type heterojunction: under the driving of the interface built-in electric field, the photo-generated carriers are directionally recombined and spatially separated, which not only greatly inhibits the recombination of electron-hole pairs and prolongs the carrier lifetime, but more importantly, selectively retains the electrons with the strongest reducing ability and the holes with the strongest oxidizing ability. This makes the material output two kinds of high-efficiency active substances under light: strong reducing electrons continuously migrate to the metal substrate, which makes it cathodically polarized, realizing efficient and stable photoelectrochemical cathodic protection; at the same time, strong oxidizing holes directly generate high-activity oxygen species on the material surface, which completely degrades organic pollutants and effectively kills attached microorganisms, thereby simultaneously realizing strong anti-fouling and bacteriostasis. This "reduction-oxidation" dual-function integrated synergistic effect fundamentally solves the contradiction that the traditional type II heterojunction cannot meet the dual needs due to the double weakening of the oxidation and reduction ability, and breaks through the bottleneck of single function of traditional technology, providing a revolutionary green solution for long-term marine protection. BRIEF DESCRIPTION OF DRAWINGS

[0018] The drawings accompanying the specification of this application are used to provide further understanding of the application, and the illustrative embodiments of the application and their descriptions are used to explain the application, and do not constitute improper limitations on the application. Among them:

[0019] Figure 1 The inhibition effect diagram of Chlorella vulgaris and Chlorella sp. on the Bi2MoO6 photoanode film of Comparative Example 1, the MnIn2S4 photoanode film of Comparative Example 2 and the S-type heterojunction photoanode film (Bi2MoO6-MnIn2S4) of Example 1;

[0020] Figure 2The electron spin resonance (ESR) curves of the NiTiO3 photoanode film of Comparative Example 3, the BiOI photoanode film of Comparative Example 4 and the S-type heterojunction photoanode film (BiOI-NiTiO3) of Example 2;

[0021] Figure 3 The potentiodynamic polarization curves of the S-type heterojunction photoanode film (CuInS2-AgI) of Example 3 coupled with steel bars (carbon steel, represented by Q235 CS in the figure) under light conditions;

[0022] Figure 4 The degradation efficiency of Rhodamine B (RhB) by the MnWO4 photoanode film of Comparative Example 5, the In2S3 photoanode film of Comparative Example 6 and the S-type heterojunction photoanode film (In2S3-MnWO4) of Example 4;

[0023] Figure 5 The photocurrent density-time (I-t) curves of the S-type heterojunction photoanode film (Bi2MoO6-MnIn2S4) of Example 1, the S-type heterojunction photoanode film (BiOI-NiTiO3) of Example 2, the S-type heterojunction photoanode film (CuInS2-AgI) of Example 3 and the S-type heterojunction photoanode film (In2S3-MnWO4) of Example 4 under intermittent light conditions. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present application will be described in detail below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art belong to the scope of protection of the present application.

[0025] The present application will be described in detail below with reference to the embodiments. It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other without conflict.

[0026] The present application aims at the contradiction that the traditional type II heterojunction of the existing photoanode material cannot meet the dual requirements due to the double weakening of the redox ability, and also breaks through the bottleneck of the single function of the traditional technology, and provides a photo-driven corrosion and pollution prevention integrated protection film and a preparation method thereof, which provides a new, green and efficient solution for the long-term protection of marine engineering facilities.

[0027] In order to achieve the above object, the present application provides the following technical scheme: a light-driven anti-corrosion and anti-fouling function integrated S-shaped heterojunction photoanode film, characterized in that it is composed of a first semiconductor material and a second semiconductor material; the conduction band bottom energy level of the first semiconductor material is lower than that of the second semiconductor material, and the valence band top energy level of the first semiconductor material is lower than that of the second semiconductor material; after Fermi energy level balance, the energy bands of the two semiconductor materials are bent at the interface, the photo-generated electrons of the second semiconductor material and the photo-generated holes of the first semiconductor material are combined to form a heterojunction structure with an S-shaped electron transfer path.

[0028] The conduction band bottom energy level of the first semiconductor material is lower than that of Fe 2+ The conduction band bottom energy level of the first semiconductor material is lower than that of Fe

[0029] The valence band top energy level of the second semiconductor material is higher than the oxidation potential of O2 / H2O (+1.23 V vs. NHE), preferably one of bismuth molybdate (Bi2MoO6), manganese tungstate (MnWO4), nickel titanate (NiTiO3) and silver iodide (AgI).

[0030] The present application also provides a preparation method of a light-driven anti-corrosion and anti-fouling function integrated S-shaped heterojunction photoanode film, which adopts the following technical scheme: (1) providing a first semiconductor precursor and a second semiconductor precursor; (2) reacting the first semiconductor precursor and the second semiconductor precursor by a hydrothermal method, a calcination method, an in-situ growth method or an ultrasonic mixing method to make the first semiconductor material and the second semiconductor material composite, thereby forming the S-shaped heterojunction photoanode film.

[0031] The reaction temperature of the hydrothermal method is preferably 120-180℃; the reaction time of the hydrothermal method is preferably 6-24 hours.

[0032] The heat treatment temperature of the calcination method is preferably 300-500℃; the holding time of the calcination method is preferably 1-4 hours.

[0033] The present application also provides an application of a light-driven anti-corrosion and anti-fouling function integrated S-shaped heterojunction photoanode film, which adopts the following technical scheme: the application of the S-shaped heterojunction photoanode film in the surface protection of metal materials.

[0034] The application is preferably to simultaneously realize the anti-corrosion and anti-fouling and algae inhibition functions in a marine environment.

[0035] The application will be described in detail below with reference to specific embodiments of a light-driven S-type heterojunction photoanode film with integrated anti-corrosion and anti-fouling functions and a preparation method thereof.

[0036] Example 1

[0037] The preparation method of the Bi2MoO6 nanosheet-MnIn2S4 quantum dot (Bi2MoO6-MnIn2S4) S-type heterojunction photoanode film of this example includes the following steps:

[0038] (1) Preparation of Bi2MoO6 nanosheets:

[0039] Bi2MoO6 nanosheets were prepared by a hydrothermal method. 1 mmol of sodium molybdate (Na2MoO4) and 2 mmol of bismuth nitrate (Bi(NO3)3) were added to 30 ml of deionized water and stirred vigorously for 30 min. The mixed solution was poured into a high-pressure reaction kettle and placed in FTO conductive glass, which was heated at 150°C for 20 h. After cooling, the FTO was removed, washed and dried to obtain FTO conductive glass loaded with Bi2MoO6 nanosheets.

[0040] (2) Complexing of MnIn2S4 quantum dots:

[0041] MnIn2S4 quantum dots were deposited on the FTO conductive glass loaded with Bi2MoO6 nanosheets obtained in step (1) by a successive ionic layer adsorption reaction (SILAR). The FTO conductive glass loaded with Bi2MoO6 nanosheets obtained in step (1) was sequentially immersed in Mn 2+ (20 mmol Mn(NO3)2 ethanol solution), In 3+ (40 mmol In(NO3)3 ethanol solution), and S 2- (80 mmol Na2S methanol solution), and each immersion was followed by washing with the corresponding solvent, which was considered as one cycle. After 15 cycles, a Bi2MoO6 nanosheet-MnIn2S4 quantum dot (Bi2MoO6-MnIn2S4) S-type heterojunction photoanode film was prepared.

[0042] Example 2

[0043] The preparation method of the BiOI nanosheet-NiTiO3 nanofiber S-type heterojunction photoanode film (BiOI-NiTiO3) of this example includes the following steps:

[0044] (1) Preparation of NiTiO3 nanofibers:

[0045] NiTiO3 nanofibers were prepared by electrospinning. 10 mmol of tetrabutyl titanate (Ti(OC4H9)4) and 10 mmol of nickel acetate (Ni(Ac)2) were dissolved in 20 ml of N,N-dimethylformamide and 20 ml of anhydrous ethanol, respectively, and stirred for 30 min. Then, the two solutions were mixed and added to 8 g of polyvinylpyrrolidone (PVP) and stirred for another 30 min. The mixed solution was transferred to a 10 ml plastic syringe, and the pushing speed was controlled at 0.5 mL / h, the voltage was applied at 18 kV, and the rotating speed of the electrospinning drum was set at 500 r / min. After 8 h, the obtained nanofibers were calcined at 600 ℃ for 4 h, and then cooled to obtain NiTiO3 nanofibers.

[0046] (2) BiOI nanosheet composite:

[0047] The NiTiO3 powder obtained in step (1) and 2 mmol of bismuth nitrate (Bi(NO3)3) were added to 20 ml of ethylene glycol and ultrasonically dispersed for 20 min. 2 mmol of potassium iodide (KI) was dissolved in 20 ml of deionized water and slowly added to the ultrasonically dispersed solution. After stirring for 24 h, the precipitate was centrifuged and washed with deionized water for 5 times, and dried at 80 ℃ under vacuum to obtain a BiOI nanosheet-NiTiO3 nanofiber (BiOI-NiTiO3) S-type heterojunction photoanode film.

[0048] Example 3

[0049] The preparation method of the CuInS2 nanosheet-AgI nanosphere (CuInS2-AgI) S-type heterojunction photoanode film of this example comprises the following steps:

[0050] (1) Preparation of CuInS2 nanosheet:

[0051] 1 mmol of copper hydroxide (Cu(OH)2), 1 mmol of indium hydroxide (In(OH)3), 2 mmol of thiourea ((NH2)2CS), 2 g of lithium chloride (LiCl), and 3 g of potassium chloride (KCl) were mixed and ground uniformly. The ground powder was placed in a muffle furnace and heated to 400 ℃ at a rate of 5 ℃ / min, and kept for 3 h. After natural cooling, it was washed with deionized water for 5 times and dried at 60 ℃ for 10 h to obtain CuInS2 nanosheet.

[0052] (2) AgI nanosphere composite:

[0053] Take 10 mmol of silver nitrate (AgNO3) and dissolve it in 20 ml of deionized water, stir for 30 min, then slowly add 10 ml of potassium iodide (KI) aqueous solution (concentration of 1 mol / L) to the solution. Add 0.5 g of CuInS2 nanosheet prepared in step (1) to the mixed solution, stir for 5 h, then centrifuge the mixed solution. Wash the precipitate and dry it in a 50°C oven to obtain a CuInS2 nanosheet-AgI nanosphere (CuInS2-AgI) S-type heterojunction photoanode film.

[0054] Example 4

[0055] The preparation method of the In2S3 nanosphere-MnWO4 nanorod (In2S3-MnWO4) S-type heterojunction photoanode film of this example includes the following steps:

[0056] (1) Preparation of MnWO4 nanorod:

[0057] Take 2 mmol of manganese chloride (MnCl2) and 2 mmol of sodium tungstate (Na2WO4) and add them to 30 ml of deionized water, stir for 30 min. Transfer the mixed solution to a high-pressure reaction kettle and place the FTO conductive glass into the reaction kettle. After heating at 160°C for 8 h, cool and remove the FTO. After washing and drying, the FTO conductive glass loaded with MnWO4 nanorods is obtained.

[0058] (2) In2S3 nanosphere complexation:

[0059] Dissolve 5 mmol of indium nitrate (In(NO3)3) and 5 mmol of thioacetamide (TAA) in 30 ml of deionized water. After stirring vigorously for 30 min, transfer the solution to a high-pressure reaction kettle and add the FTO conductive glass loaded with MnWO4 nanorods from step (1) to it. After assembly, place the reaction kettle in an oven and heat it at 180°C for 10 h. After natural cooling, rinse the FTO with deionized water and dry it at 60°C to obtain an In2S3 nanosphere-MnWO4 nanorod (In2S3-MnWO4) S-type heterojunction photoanode film.

[0060] Comparative Example 1

[0061] The preparation method of the Bi2MoO6 photoanode film of this comparative example differs from that of Example 1 only in that step (2) is omitted; the rest is the same as Example 1.

[0062] Comparative Example 2

[0063] The preparation method of the MnIn2S4 photoanode film of this comparative example differs from that of Example 1 only in that step (1) is omitted; the substrate is clean FTO conductive glass; the rest is the same as Example 1.

[0064] Comparative Example 3

[0065] The preparation method of the NiTiO3 photoanode film in this comparative example differs from that in Example 2 only in that step (2) is omitted; the rest is the same as in Example 2.

[0066] Comparative Example 4

[0067] The preparation method of the BiOI photoanode film in this comparative example differs from that in Example 2 only in that step (1) is omitted; the NiTiO3 nanofibers obtained in step (1) are not added; the rest is the same as in Example 2.

[0068] Comparative Example 5

[0069] The preparation method of the MnWO4 photoanode film in this comparative example differs from that in Example 4 only in that step (2) is omitted; the rest is the same as in Example 4.

[0070] Comparative Example 6

[0071] The preparation method of the In2S3 photoanode film in this comparative example differs from that in Example 4 only in that step (1) is omitted; the substrate is a clean FTO conductive glass; the rest is the same as in Example 4.

[0072] Experimental Example

[0073] 1. Anti-algae experiments were conducted on the S-type heterojunction photoanode film (Bi2MoO6-MnIn2S4) of Example 1, the Bi2MoO6 photoanode film of Comparative Example 1, and the MnIn2S4 photoanode film of Comparative Example 2:

[0074] In the anti-algae experiment, *Chlorella* and *Synechococcus* were selected as the experimental algae species and added to treated seawater to prepare an algae solution. After adjusting the algae solution to an initial absorbance of 0.1, 50 mL of each solution was placed in a petri dish containing the sample. The culture environment was set at a light intensity of 4000 lx, a temperature of 20℃, and a light-dark cycle of 12:12 h. After 7 days, samples were taken to measure the absorbance values ​​and convert them to algae concentration. The algae resistance of the samples was evaluated by comparing the difference in algae concentration between the experimental group and the control group.

[0075] Results of anti-algae experiments as follows Figure 1 Show; from Figure 1It can be seen that the Bi2MoO6 photoanodic membrane of Comparative Example 1, the MnIn2S4 photoanodic membrane of Comparative Example 2, and the S-type heterojunction photoanodic membrane (Bi2MoO6-MnIn2S4) of Example 1 all exhibited certain anti-algae properties. However, the S-type heterojunction photoanodic membrane (Bi2MoO6-MnIn2S4) of Example 1 showed inhibition efficiencies of 87.23% and 91.17% against Chlorella and Synechococcus, respectively, significantly higher than the inhibition rates of the Bi2MoO6 photoanodic membrane of Comparative Example 1 and the MnIn2S4 photoanodic membrane of Comparative Example 2, indicating that the composite photoanodic membrane of Example 1 had the best anti-algae performance. This demonstrates that the construction of the S-type heterojunction retains strong redox activity, effectively inhibiting algal growth.

[0076] 2. Electron spin resonance (ESR) tests were performed on the S-type heterojunction photoanode film (BiOI-NiTiO3) of Example 2, the NiTiO3 photoanode film of Comparative Example 3, and the BiOI photoanode film of Comparative Example 4:

[0077] Electron spin resonance (ESR) tests were performed using a German Bruker EMXnano instrument, with DMPO selected as the free radical scavenger.

[0078] Test results are as follows Figure 2 As shown; from Figure 2 It can be seen that the S-type heterojunction photoanode film (BiOI-NiTiO3) in Example 2 exhibits the strongest ESR signal, indicating that the S-type heterojunction photoanode film (BiOI-NiTiO3) in Example 2 generates the most free radicals, and DMPO can capture the most free radicals. This shows that the construction of the S-type heterojunction promotes the effective separation of photogenerated electrons and holes, and retains the strong redox capability of the semiconductor material.

[0079] 3. Under illumination, the S-type heterojunction photoanode film (CuInS2-AgI) of Example 3 was coupled to a steel bar (carbon steel, represented by Q235 CS in the figure), and the potentiodynamic polarization curve was tested:

[0080] The potentiodynamic polarization curve test uses a three-electrode connection system, with the test range set to -0.6V to 0.6V relative to the open circuit potential, and the scan rate set to 1mV / s.

[0081] Test results are as follows Figure 3 As shown; from Figure 3It can be seen that under illumination, the self-corrosion potential of the reinforcing steel (carbon steel) is -0.65V; however, after coupling with the S-type heterojunction photoanode film (CuInS2-AgI) of Example 3, the corrosion potential of the reinforcing steel shifts negatively to -1.02V, indicating that the S-type heterojunction photoanode film (CuInS2-AgI) of Example 3 can provide effective cathodic protection for the reinforcing steel (carbon steel) through photoelectric conversion. This demonstrates that the presence of the S-type heterojunction enhances the photocathodic protection performance of the semiconductor, providing better protection for the metal.

[0082] 4. Photocatalytic degradation of Rhodamine B (RhB) was tested on the S-type heterojunction photoanode film (In2S3-MnWO4) of Example 4, the MnWO4 photoanode film of Comparative Example 5, and the In2S3 photoanode film of Comparative Example 6:

[0083] In the photocatalytic degradation experiment of RhB, a 300W xenon lamp was used as the light source, and a 10 mg / L RhB aqueous solution was selected as the degradation solution. During the experiment, 5 ml of the reaction solution was taken every 10 minutes of illumination, and the RhB content was measured using a spectrophotometer.

[0084] Test results are as follows Figure 4 As shown; from Figure 4 It can be seen that after 50 minutes of illumination, the degradation rates of RhB by the MnWO4 photoanode membrane in Comparative Example 5 and the In2S3 photoanode membrane in Comparative Example 6 were 20.8% and 68.9%, respectively. However, the RhB degradation efficiency of the S-type heterojunction photoanode membrane (In2S3-MnWO4) in Example 4 was 97.1%, significantly higher than that of the MnWO4 photoanode membrane in Comparative Example 5 and the In2S3 photoanode membrane in Comparative Example 6. This indicates that the S-type heterojunction photoanode membrane (In2S3-MnWO4) in Example 4 possesses superior water purification performance, and the construction of the S-type heterojunction can effectively enhance the degradation capacity of the photoanode membrane for pollutants.

[0085] 5. The S-type heterojunction photoanode film (Bi2MoO6-MnIn2S4) of Example 1, the S-type heterojunction photoanode film (BiOI-NiTiO3) of Example 2, the S-type heterojunction photoanode film (CuInS2-AgI) of Example 3, and the S-type heterojunction photoanode film (In2S3-MnWO4) of Example 4 were coupled to steel bars (carbon steel), and the photocurrent density-time change (It) curves were tested under intermittent illumination conditions.

[0086] Photocurrent density-time variation (It) measurements were performed using a Gamry Interface 5000E electrochemical workstation. The tests were conducted in a dual-electrolytic cell system, using a 300W xenon lamp to simulate sunlight and a 3.5wt% NaCl solution as the electrolyte.

[0087] Test results are as follows Figure 5 As shown; from Figure 5 It can be seen that the photocurrent density of the S-type heterojunction photoanode film (Bi2MoO6-MnIn2S4) in Example 1 is 43.08 μA·cm. -2 The photocurrent density of the S-type heterojunction photoanode film (BiOI-NiTiO3) in Example 2 is 40.81 μA·cm. -2 The photocurrent density of the S-type heterojunction photoanode film (CuInS2-AgI) in Example 3 is 41.37 μA·cm. -2 The photocurrent density of the S-type heterojunction photoanode film (In2S3-MnWO4) in Example 4 is 48.25 μA·cm. -2 The high photocurrent density of the S-type heterojunction composite photoanode films in Examples 1-4 indicates that they all have high efficiency in separating photogenerated electron-hole pairs, and can provide excellent photocathode protection for metals.

[0088] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. An S-type heterojunction photoanode film integrating light-driven anti-corrosion and anti-fouling functions, characterized in that, It is composed of a first semiconductor material and a second semiconductor material; The conduction band bottom energy level of the first semiconductor material is negative than the conduction band bottom energy level of the second semiconductor material, and the valence band top energy level of the first semiconductor material is negative than the valence band top energy level of the second semiconductor material; After reaching Fermi level equilibrium, the energy bands of the two semiconductor materials bend at the interface, and photogenerated electrons from the second semiconductor material recombine with photogenerated holes from the first semiconductor material to form a heterojunction structure with an S-shaped electron transfer path.

2. The S-type heterojunction photoanode film with integrated light-driven anti-corrosion and anti-fouling functions according to claim 1, characterized in that, The first semiconductor material's conduction band bottom energy level is negative to Fe 2+ / Fe reduction potential (-0.44V vs. NHE).

3. The S-type heterojunction photoanode film with integrated light-driven anti-corrosion and anti-fouling functions according to claim 1 or 2, characterized in that, The valence band top energy level of the second semiconductor material is positive to the oxidation potential of O2 / H2O (+1.23V vs. NHE).

4. A method for preparing an S-type heterojunction photoanode film with integrated light-driven anti-corrosion and anti-fouling functions as described in any one of claims 1-3, characterized in that, The process includes the following steps: (1) providing a first semiconductor precursor and a second semiconductor precursor; (2) reacting the first semiconductor precursor and the second semiconductor precursor by hydrothermal method, calcination method, in-situ growth method or ultrasonic mixing method to combine the first semiconductor material with the second semiconductor material to form the S-type heterojunction photoanode film.

5. The method according to claim 4, characterized in that, The hydrothermal method has a reaction temperature of 120-180℃ and a reaction time of 6-24 hours.

6. The method according to claim 4, characterized in that, The heat treatment temperature of the calcination method is 300-500℃, and the holding time is 1-4 hours.

7. The application of an S-type heterojunction photoanode film as described in any one of claims 1-3 in the surface protection of metallic materials.

8. The application according to claim 7, characterized in that, The application aims to simultaneously achieve anti-corrosion, anti-fouling, and algae-suppressing functions in a marine environment.

Citation Information

Patent Citations

  • Bismuth oxyiodide / bismuth molybdate composite photocatalyst and preparation method thereof

    CN104190450A

  • Development and application of novel steric-hindrance-adjustable-and-controllable visible light photoelectric chemical detection PFOA (perfluorooctanoic acid) sensor

    CN104880495A

  • S-type heterojunction composite photo-anode film and preparation method and application thereof

    CN114703481A

  • Ni2P / TiO2 S-type heterojunction photo-anode material and application

    CN115613037A

  • A method for synthesis of green bismuth molybdate and its composites

    IN201811026610A